Predicción de la Resistencia de las Conexiones Tipo Canal en Estructuras Compuestas de Acero y Hormigón - Quevedo, Rafael Larrúa; Vergara, Ramiro Vargas; Louzado, Jennifer Espino (KnE Engineering, 2018)
This article deals with channel connections in steel and concrete composite structures, with the main objective of obtaining a new formulation to determine the resistance of this widely used type of connection in the American region. Data from channel connections tests are collected from reliable experimental and numerical sources, and a valid database is created to make predictions by means of different combinations of artificial intelligence techniques, to obtain the most effective cases. Finally, a new formulation is proposed to calculate the resistance of channel connections in solid slab, applying statistical techniques to a database that incorporates experimental, numerical and artificial intelligence results, demonstrating its superiority with respect to the existing formulations in the international literature, by means of statistical measures appropriately applied to the studied case. The proposed methodology is novel and effective, and it can be expanded to other types of structural elements. Keywords: composite structures, connections, resistance, prediction.